2012
DOI: 10.1093/cercor/bhs190
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Synchrony During Early Alcohol Abstinence Can Predict Subsequent Relapse

Abstract: Short-term abstinent alcoholics have shown increased engagement of reward regions and reduced engagement of executive control regions. There is no report yet on whether these differences can predict relapse. This is the first study that investigates whether differences in resting-state networks can predict later relapse. Resting-state functional magnetic resonance imaging data were collected from 69 short-term abstinent alcoholics. Participants performed the affective go/no-go task outside of the scanner. At 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
108
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 62 publications
13
108
1
Order By: Relevance
“…However, Chanraud et al (2011) reported that controls (n=15) had more positive resting state connectivity within the default mode network that ALC subjects (n=15) which we did not find. Further Camchong et al (2012) found than relapsing alcoholics (n=29) had lower connectivity within not only the ECNs, but also within reward, visual and salience networks than abstainers (n=40), networks where we did not find significant effects, possibly attributable to our large sample of subjects with varying degrees of disorder. Our study also did not include follow up data for evaluation of relapse, however, given the finding that measures of severity were associated with degradation of network integrity only within the LECN across 383 ALC subjects, the negative impact of chronic alcohol use on this control system may be critically important in the addiction cycle.…”
Section: Discussioncontrasting
confidence: 59%
“…However, Chanraud et al (2011) reported that controls (n=15) had more positive resting state connectivity within the default mode network that ALC subjects (n=15) which we did not find. Further Camchong et al (2012) found than relapsing alcoholics (n=29) had lower connectivity within not only the ECNs, but also within reward, visual and salience networks than abstainers (n=40), networks where we did not find significant effects, possibly attributable to our large sample of subjects with varying degrees of disorder. Our study also did not include follow up data for evaluation of relapse, however, given the finding that measures of severity were associated with degradation of network integrity only within the LECN across 383 ALC subjects, the negative impact of chronic alcohol use on this control system may be critically important in the addiction cycle.…”
Section: Discussioncontrasting
confidence: 59%
“…Another noteworthy phenomenon is that most former studies on MMT have been cross-sectional, preventing investigators from adequately controlling for possible effects of previous addictive drug use. Understanding whether and how MMT affects inhibitory control function is essential for improving efficacy, which is particularly important, as therapy is associated with a relatively high rate of relapse (15).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, neuroscientists have suggested that endophenotypes carry the potential to characterize underlying traits and abnormalities independently of behavioral phenotypes (5). This stance has been supported by recent functional MRI (fMRI) studies that have, for instance, accurately predicted choices in a motor-decision task (6), substance abuse relapse (7)(8)(9)(10), and consumer purchases (i.e., neuromarketing) (11). These results raise the possibility that more direct measures of brain activity associated with impulse control may lend incremental utility to the prediction of future antisocial behavior.…”
mentioning
confidence: 96%